(Lifestyle) immigrant entrepreneurs in Spanish small villages: Rethinking international immigration in rural Alt Empordà, Catalonia - Cristóbal Mendoza; Ricard Morén-Alegret; Ruth McAreavey (Belgeo)
The article studies connections between local economics, entrepreneurship and lifestyle immigration in municipalities with fewer than 500 inhabitants in Alt Empordà, Spain. Using a qualitative methodology, it analyses the economic incorporation of immigrant entrepreneurs by considering in which ways they contribute to the local economies. It also studies to what extent immigrant businesses follow purely economic benefit logics (or rather they are set up in search of a better quality of life). The interviewed immigrant entrepreneurs usually fit themselves in distinctive niches in local labour markets (e.g. cultural-oriented services). Their success partially relies in their capacities for creating locally based social networks, which are not only key aspects for business development, but also a source of wellbeing. This is in line with most lifestyle immigration literature, which argues that immigration is not only triggered by professional success, but also represents the search for self-realization and a higher quality of life.